Randomized phase II study evaluating a carbon ion boost applied after combined radiochemotherapy with temozolomide versus a proton boost after radiochemotherapy with temozolomide in patients with primary glioblastoma: the CLEOPATRA trial - Combs, Stephanie; Kieser, Meinhard; Rieken, Stefan; Habermehl, Daniel; Jäkel, Oliver; Haberer, Thomas; Nikoghosyan, Anna; Haselmann, Renate; Unterberg, Andreas; Wick, Wolfgang; Debus, Jürgen (BMC cancer, 2010)
BACKGROUND: Treatment standard for patients with primary glioblastoma (GBM) is combined radiochemotherapy with temozolomide (TMZ). Radiation is delivered up to a total dose of 60 Gy using photons. Using this treatment regimen, overall survival could be extended significantly however, median overall survival is still only about 15 months. Carbon ions offer physical and biological advantages. Due to their inverted dose profile and the high local dose deposition within the Bragg peak precise dose application and sparing of normal tissue is possible. Moreover, in comparison to photons, carbon ions offer an increase relative biological effectiveness (RBE), which can be calculated between 2 and 5 depending on the GBM cell line as well as the endpoint analyzed. Protons, however, offer an RBE which is comparable to photons. First Japanese Data on the evaluation of carbon ion radiation therapy showed promising results in a small and heterogeneous patient collective. - METHODS/DESIGN: In the current Phase II-CLEOPATRA-Study a carbon ion boost will be compared to a proton boost applied to the macroscopic tumor after surgery at primary diagnosis in patients with GBM applied after standard radiochemotherapy with TMZ up to 50 Gy. In the experimental arm, a carbon ion boost will be applied to the macroscopic tumor up to a total dose of 18 Gy E in 6 fractions at a single dose of 3 Gy E. In the standard arm, a proton boost will be applied up to a total dose 10 Gy E in 5 single fractions of 2 Gy E. Primary endpoint is overall survival, secondary objectives are progression-free survival, toxicity and safety. - DISCUSSION: The Cleopatra Trial is the first study to evaluate the effect of carbon ion radiotherapy within multimodality treatment of primary glioblastoma in a randomized trial comparing this innovative treatment of the treatment standard, consisitng of photon radiotherapy in combination with temozolomide. - TRIAL REGISTRATION: ISRCTN37428883 and NCT01165671.